Unheard voices: Smokers' support for anti-smoking campaigns - Mohd Haazik Mohamed; Yessy Octavia Misdi; Razima Hanim Osman; Najah Afina Mohd Harun; Wanda Kiyah George Albert (RSIS International, 2025)
Tobacco use remains a significant global public health challenge, with considerable health, social, and economic consequences. In Malaysia, anti-smoking campaigns like the long-standing "Tak Nak Merokok" and the 2019 "Speak Out" campaign have raised awareness about smoking dangers, with "Speak Out" empowering non-smokers to reprimand smokers and protect themselves. However, understanding smokers' attitudes toward these campaigns is essential for improving their effectiveness. This study aims to investigate smokers' perception of anti-smoking campaigns that encourage people to stand up, reprimand smokers who smoke around them, and protect themselves from secondhand and thirdhand smoke, as well as the factors that influence these perceptions. Data were collected from a survey conducted by the Health Education Division, Ministry of Health Malaysia, in 2019, involving 3,453 respondents aged 18 and above, with 217 identifying as smokers. The survey examined respondents' smoking behaviours, awareness of secondhand and thirdhand smoke, and their outrage to reprimand smokers who smoke in public places spaces. Descriptive and inferential statistical analyses were performed using IBM SPSS Statistics version 25. The results revealed significant differences in attitudes based on demographic factors and smoking behaviours. Younger respondents were more likely to support reprimanding smokers in public, while those with family members or housemates who smoked were less willing to take action. Awareness of the dangers of secondhand and thirdhand smoke significantly influenced respondents' likelihood to reprimand smokers. Logistic regression analysis identified key predictors, with respondents who perceived secondhand smoke as harmful being six times more likely to reprimand smokers in public. These findings emphasize the importance of considering demographic and behavioural factors in the design of future anti-smoking campaigns, offering valuable insights to enhance their reach and impact in reducing smoking prevalence in Malaysia.